2018
DOI: 10.1634/theoncologist.2018-0117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Age on Molecular Alterations of Left-Sided Colorectal Tumors

Abstract: The increasing rate of colorectal cancers (CRC), primarily distal tumors, among young adults poses a global health issue. This study investigates the molecular differences between younger (≤45 years old) and older (≥65) adults with left-sided CRCs. Younger patients more frequently harbor mutations in genes associated with cancer-predisposing syndromes. Higher rates of microsatellite instability-high and tumor mutational burden-high tumors occur in younger patients, who could benefit from immune-checkpoint inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 49 publications
(72 reference statements)
0
26
0
Order By: Relevance
“…Furthermore, genes responsible for histone modification and chromatin remodeling, such as KMT2D and ARID1A, were more frequently mutated in RT compared with LT. Interestingly, in our previous analysis focused on the molecular characterization of left-sided CRC in AYA versus older adults, we highlighted an increased incidence of mutations in genes involved in histone modification in AYA compared with older patients with CRC, including KDM5C, KMT2A, KMT2C, KMT2D, and SETD2 [28]. Hence, disruption of the histone modification pathway appears to be a distinctive feature of CRC in AYA and to be more prominent in RT in our population.…”
Section: Protein Expression and Gene Amplificationmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, genes responsible for histone modification and chromatin remodeling, such as KMT2D and ARID1A, were more frequently mutated in RT compared with LT. Interestingly, in our previous analysis focused on the molecular characterization of left-sided CRC in AYA versus older adults, we highlighted an increased incidence of mutations in genes involved in histone modification in AYA compared with older patients with CRC, including KDM5C, KMT2A, KMT2C, KMT2D, and SETD2 [28]. Hence, disruption of the histone modification pathway appears to be a distinctive feature of CRC in AYA and to be more prominent in RT in our population.…”
Section: Protein Expression and Gene Amplificationmentioning
confidence: 72%
“…There were also greater frequencies of MSI-high (MSI-H) status and high tumor mutational burden (TMB). Additionally, mutations in genes involved in histone modification were found to be significantly increased compared with older patients with CRC [28].…”
Section: Introductionmentioning
confidence: 99%
“…In this study tumour mutation burden was also evaluated by the authors . A high level of mutations (TMB-High>17 mutation/Mb) wass observed more often in patients with EOCRC (9.7% vs 2.8%, p<0.001) [3].…”
Section: Microsatellite Stable (Mss)-crc and Chromosome Unstable Waysmentioning
confidence: 88%
“…Whole-exome sequencing of tumour samples in different patient groups (under 45 years and older 65 years) did not reveal significant differences in the spectrum of genes with a high rate of mutations. In both cohorts, the rate of somatic mutations in the genes APC was 81.8%, TP53 -74.6%, KRAS -46.4%, ARID1A -19.4%, PIK3CA -13.4%, FBXW7 -11.2%, SMAD4 -10.1%, ATM -6.3%, NRAS -4.9%, BRAF -4.6%[3], while the somatic status of the genes responsible for hereditary CRC differed and was characterized by the prevalence of mutations in patients with EOCRC including the genes MSH6 (4.8% vs 1.2%, p=0.005), MSH2 (2.7% vs 0.0%, p=0.004), POLE (1.6% vs 0.0%, p=0.008), NF1 (5.9% vs 0.5%, p<0.001), SMAD4 (14.3% vs 8.3%, p=0.024), PTEN (4.3% vs 1.4%, p=0.03), TSC1 (1.1% vs 0.0%, p=0.031), TSC2 (1.6% vs 0.2%, p=0.048)[3].…”
mentioning
confidence: 98%
“…But in the TCGA and Seshagiri dataset, higher correlations were observed (TCGA, R 2 =0.9978; Seshagiri, R 2 =0.9948), which indicated that include all point mutations in the calculation of TMB may even enhance the precision of the estimation to some extent. And there also is no agreed on the objective cut-points for TMB, so we defined TMB-high as ≥17 mut/Mbp [29,52] and ≥12 mut/Mbp [4,53] to investigate the molecular characteristics of patients with different TMB levels. Unexpectedly, similar molecular differences were found between the TMB-high and TMB-low group ( Supplementary Table S2 and Table S3).…”
Section: Discussionmentioning
confidence: 99%